2010
DOI: 10.1186/1471-2199-11-37
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel transforming growth factor-beta (TGF-beta6) gene in fish: regulation in skeletal muscle by nutritional state

Abstract: Background:The transforming growth factor-β (TGF-β) family constitutes of dimeric proteins that regulate the growth, differentiation and metabolism of many cell types, including that of skeletal muscle in mammals. The potential role of TGF-βs in fish muscle growth is not known. Results:Here we report the molecular characterization, developmental and tissue expression and regulation by nutritional state of a novel TGF-β gene from a marine fish, the gilthead sea bream Sparus aurata. S. aurata TGF-β6 is encoded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 78 publications
1
18
0
1
Order By: Relevance
“…Subsequently all three homologues of the mammalian TGF-b ligands were found in several teleost species [155e166]. Recently, a novel isoform, TGF-b6, so far only discovered in fish, was cloned from the gilthead sea bream [167]. However, the evolutionary origin of this isoform needs to be confirmed in other fish species.…”
Section: Tgf-b1mentioning
confidence: 99%
“…Subsequently all three homologues of the mammalian TGF-b ligands were found in several teleost species [155e166]. Recently, a novel isoform, TGF-b6, so far only discovered in fish, was cloned from the gilthead sea bream [167]. However, the evolutionary origin of this isoform needs to be confirmed in other fish species.…”
Section: Tgf-b1mentioning
confidence: 99%
“…Our results revealed that the TGF-β1 expression in male was lower than in female among most tissues except spleen and gills. Spleen as an important immune organ in teleosts generates a great amount of TGF-β that plays a key role in fish skeletal muscle development (Yang & Zhou, 2008;Funkenstein Olekh, & Jakowlew, 2010). High level of TGF-β1 expression also has been found in the gill of sea bream (Sparus aurata) (Tafalla et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional change also affects muscle mass through the regulators of muscle growth and development. Several in vitro studies indicate that starving and lack of essential nutrients for muscle growth stimulate myostatin expression in fish [ 42 44 ]. Therefore, using in vitro experiments it is difficult to determine whether myostatin upregulation in viral infected animals is triggered by immune response or lack of nutrients due to loss of appetite.…”
Section: Discussionmentioning
confidence: 99%